2022
DOI: 10.1016/j.econedurev.2021.102198
|View full text |Cite
|
Sign up to set email alerts
|

Only a matter of time? The role of time in school on four-day school week achievement impacts

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…The Goodman-Bacon (2021) decomposition of the weights on each two-group by two-period (2 × 2) pair also shows that the share of the overall weighting placed on comparisons between "timing groups" (districts who ever adopted a 4-day school week) and "nevertreated groups" was greater than 97% for all subsamples, further indicating that the issues related to variation in treatment timing for TWFE DID estimators are not likely to affect the original estimates herein. This result was similar to that of Thompson and Ward (2022), who used the same procedure and found that the weighting placed on the same comparisons was between 95% and 99% for all of their analyses. A graphical example of this decomposition exercise for the math ACT analysis in this study is presented in Supplementary Figure A6 in the online version of the journal.…”
Section: Robustness Checkssupporting
confidence: 83%
See 4 more Smart Citations
“…The Goodman-Bacon (2021) decomposition of the weights on each two-group by two-period (2 × 2) pair also shows that the share of the overall weighting placed on comparisons between "timing groups" (districts who ever adopted a 4-day school week) and "nevertreated groups" was greater than 97% for all subsamples, further indicating that the issues related to variation in treatment timing for TWFE DID estimators are not likely to affect the original estimates herein. This result was similar to that of Thompson and Ward (2022), who used the same procedure and found that the weighting placed on the same comparisons was between 95% and 99% for all of their analyses. A graphical example of this decomposition exercise for the math ACT analysis in this study is presented in Supplementary Figure A6 in the online version of the journal.…”
Section: Robustness Checkssupporting
confidence: 83%
“…Finally, he also demonstrates that the observed negative average effects on math and ELA achievement in his study can be attributed, at least in part, to 4-day schools' average 3.5 fewer hours of time students spend at school per week compared to the 5-day schools in his sample. Similarly, Thompson and Ward (2022) find that significant, negative effects of the 4-day week on math and ELA achievement are borne only by 4-day week districts that were in the lowest tercile of "time in school," measured as weekly instructional hours.…”
Section: Academic Achievementmentioning
confidence: 91%
See 3 more Smart Citations